2017
DOI: 10.1111/ejss.12439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of roots and easily available carbon on the decomposition of soil organic matter fractions in boreal forest soil

Abstract: The priming effect induced by carbon (C) that is easily available to microbes has been shown to increase the mineralization of soil organic matter (SOM) that is resistant to decomposition, but the combined effects of easily available carbon and the living root system have rarely been studied. The aim of this research was to study the decomposition of SOM fractions of different solubility in water and their 13C, 14C and 15N abundance with and without the presence of a living root system and easily available car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Collection of the soil took place 3–4 weeks before the microcosms were set up and this disturbance, coupled with subsequent homogenization, may have resulted in mineralization of the easily available organic matter fraction (Pumpanen et al ., ) and destruction of mycorrhizal mycelium deriving C from intact connections with tree hosts, resulting in changes in fungal community structure (Lindahl et al ., ). However, mycorrhizal colonization of roots occurred rapidly (within five days), suggesting that the inoculum potential of the soil was still high, and reproducible differences in community structure were found.…”
Section: Discussionmentioning
confidence: 99%
“…Collection of the soil took place 3–4 weeks before the microcosms were set up and this disturbance, coupled with subsequent homogenization, may have resulted in mineralization of the easily available organic matter fraction (Pumpanen et al ., ) and destruction of mycorrhizal mycelium deriving C from intact connections with tree hosts, resulting in changes in fungal community structure (Lindahl et al ., ). However, mycorrhizal colonization of roots occurred rapidly (within five days), suggesting that the inoculum potential of the soil was still high, and reproducible differences in community structure were found.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also noted that burning of the depleted litter is not necessarily the most dominating reason for enrichment with heavier isotopes. Instead, the enrichment may be attributed to volatilisation processes, which discriminate against heavier isotopes (Cook 2001;Boeckx et al 2005) and root activity (Pumpanen et al 2017). Forest fires generally also increase N leaching (Lamontagne et al 2000), especially the leaching of 15 N depleted NO 3- (Pardo et al 2002), which may have contributed to 15 N enrichment in the FIRE 3 area.…”
Section: Discussionmentioning
confidence: 99%
“…One important source of uncertainty regarding priming effects is which components of SOM are primed. Jussi Heinonsalo (University of Helsinki, Finland) analyzed the influence of pine roots on the decomposition of SOM originating from the organic horizon of a boreal forest (Pumpanen et al, 2017). They showed that roots changed C and N pools in the soluble SOM fraction.…”
Section: Forest Rhizosphere Ecology and Biogeochemistrymentioning
confidence: 99%